Pengaruh Citra Merek, Kualitas Produk Dan Kepercayaan Terhadap Keputusan Pembelian Pada E-Commerce Shopee - Apriati Nababan; Asron Saputra (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine whether brand image, product quality and trust variables influence purchasing decisions at e-commerce shopee. The population used in this study were residents who live in the Muka Kuning Indah 1 housing complex. The number of samples used was 120 people, the samples were taken using the non-probability sampling method and the instrument used was purposive sampling. The data collection method used was a questionnaire with a Likert scale. SPSS version 26 is used to process data. The results of this study indicate that brand image partially has a significant effect on purchasing decisions at shopee as indicated by the t count (3.150) > t table (1.980) and the sig value 0.002 <0.05. Partially product quality has no significant effect on purchasing decisions on e-commerce shopee as evidenced by the t count (-0.412) < t table (1.980) and is significant 0.681 > 0.05. Trust partially has a significant effect on purchasing decisions on e-commerce shopee as evidenced by the t count (7.387) > t table (1.980) and the sig value 0.000 <0.05. Brand image, product quality and trust simultaneously influence purchasing decisions on e-commerce shopee with an F count (59.588) > F table (2.68) and a sig value of 0.000 <0.05. The adjusted R square value of 0.596 or 59.6% of the independent variables affects the dependent variable while the remaining 40.4% is influenced by other variables not present in this study.